(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
FDI may be defined as an investment involving a lasting interest and control by an investor who is a resident of another economy, other than that of the host economy. In the simple sense, FDI implied that the investor has a significant degree of influence on the management. Foreign Direct Investments are investments made by residents of one economy with the objective of establishing a lasting interest in a company located in another economy (host economy).FDI refers to the purchase by the citizens of one country of non-financial assets in another country. Foreign direct investment involves the acquisition or establishment of a firm, company or enterprise in a country outside of the registered corporate home country. FDI in real estate involves acquisition of land or building across all commercial, residential and retail segments. Any construction activity is also included in FDI.